'Phaco–ECP': combined endoscopic cyclophotocoagulation and cataract surgery to augment medical control of glaucoma. Issue 3 (30th May 2012) - Lindfield, Dan; Ritchie, Robert W; Griffiths, Michael FP
Abstract : Objectives: Does phaco–ECP reduce intraocular pressure? Is phaco–ECP safe? Design: Retrospective case note review of all patients undergoing phaco–ECP between June 2008 and June 2009. All glaucoma subtypes were included. Setting: Single District General Hospital Ophthalmology Department within the UK. Participants: 58 participants case notes reviewed. Mean age 79.0 years (SD ±9.8). Interventions: All patients received combined cataract surgery and endoscopic cyclophotocoagulation. Outcome measures: Follow-up was 1 day, 1 week, 1, 3, 6, 12, 18 and 24 months for intraocular pressure (IOP) measurement. Number of medications, visual acuity and presence of complications were also assessed. Results: Of the 58 cases performed, 56 case notes (97%) were available for analysis. Mean age 79.0 years (SD ±9.8). Mean pre-procedural IOP was 21.54 mm Hg (95% CI 19.86 to 23.22, n=56). Mean IOP was 14.43 mm Hg (95% CI 13.65 to 15.21, n=53) at 18 months and 14.44 mm Hg (95% CI 13.63 to 15.25, n=41) at 24 months. The mean drop from baseline to 18 and 24 months was 7.1 mm Hg. Statistically significant decrease in IOP was demonstrated at all time points (p<0.001). Mean medication usage was 1.97 agents (95% CI 1.69 to 2.25) at baseline, 1.96 agents (95% CI 1.70 to 2.22) at 18 months and 2.07 agents (95% CI 1.76 to 2.38) at 24 months. No statistically significant change throughout. Conclusions: This study confirms the safety of phaco–ECP. In this case series, the IOP-lowering effect was significant at all time points; however, the effect of cataract surgery alone was not controlled. A randomised controlled trial is required to draw efficacy conclusions. The authors proposed endoscopic cyclophotocoagulation's main role is to optimise control of low-risk glaucoma of low-risk patients at the time of cataract surgery. However, the authors do not propose that phaco–ECP is a substitute for filtration surgery in high-risk eyes or when low target pressures (<14 mm Hg) are indicated.